State of Knowledge on Beekeeping in Côte d’Ivoire: Challenges and Opportunities for Sustainable Productivity of the Sector in the Context of Climate Change - Ouattara, Salimata; Assi-Kaudjhis, Chimène; Adjonou, Kossi; Kouamé, Koffi Félix; Koudegnan, Comlan Mawussi; Kokou, Kouami (European Scientific Journal, ESJ, 2023)
The beekeeping sector in Côte d’Ivoire is developing. Honey gathering, traditional beekeeping and modern beekeeping are widespread in the centre and north of the country. They enable the populations of these areas to diversify and increase their income, and to cure certain benign diseases. Côte d’Ivoire honeys are of good quality and very rich in nutrients: pollen grains and minerals. Despite favourable climatic and floristic conditions, beekeeping in Côte d’Ivoire is still in its infancy, with the aim of increasing honey production. The population of Côte d’Ivoire does not keep bees and is more interested in cash crops than beekeeping. The aim of this study is to take stock of the Ivorian beekeeping sector and its melliferous potential on the basis of available scientific data. The aim is to gain a better understanding of the difficulties facing the sector in terms of sustainable development.